Pakistan, society and politics - Nayak, Pandav; University of Rajasthan. South Asia Studies Centre (New Delhi : South Asian Publishers, 1984)
Papers presented at a seminar organized by South Asia Studies Centre, University of Rajasthan, 1982.
Includes bibliographical references.
Keywords: Pakistan -- Politics and government -- Congresses